The bringer of light: the raven in Inuit tradition - Oosten, Jarich; Laugrand, Frédéric (Polar Record, 2006)
In the western Arctic and in the northwest coast and Alaska, the significance of the raven as a creator and trickster is generally acknowledged. In the eastern Arctic there are no such elaborate mythical cycles concerning the bird. But the raven still plays an important role in myths and rituals. In this paper, some features of the Alaskan complex and the position of the raven in the eastern Arctic are discussed. The basic features of the Alaskan raven complex are used as heuristic principles guiding research into the situation in the eastern Arctic region. It is argued that in many respects the raven is responsible for society but without being part of it. As a predator and a scavenger it is often associated with eating dirt, excrement and human flesh, and yet it created light, enabling people to see and invented tattooing, enabling women to marry.